Raiva em bovino associada a intoxicação espontânea por Sida carpinifolia - Casagrande, Renata Assis (2012)
Two female bovine, crossbreed, 6-year-old (case 1) and 18-month-old (case 2) grazing in pasture infested by Sida carpinifolia showed gait difficulties, initially at the pelvic limbs, progressing to sternal or lateral decumbency, nystagmus, tremors, and fasciculation of the head for four to five days. Histologically was observed meningoencephalitis and ganglioneuritis nonsuppurative with Negri corpuscles in the neurons of the cerebellum, brain steam, hippocampus, trigeminal ganglion and spinal cord. Another histological finding was a cytoplasmic vacuolation of the Purkinje cells and in the trigeminal ganglion neurons. Direct immunofluorescence (DIF) for rabies viral antigen was positive in both animals and anti-rabies immunohistochemistry (IHC) was positive in the neurons of the cerebellar and cerebral cortex, hippocampus, and trigeminal ganglion. Con-A, WGA, and sWGA lectin histochemistry were positive in the vacuolated neurons. Based on the morphological and epidemiological features, rabies DIF and IHC, and lectin histochemistry the present report consists of two cases of subclinical poisoning with S. carpinifolia in cattle infected with rabies virus.